PTI-1: novel way to oncogenicity - Vislovukh, A.A.; Shalak, V.F.; Savytskyi, O.V.; Kovalenko, N.I.; Gralievska, N.L.; Negrutskii, B.S.; El’skaya, A.V. (Вiopolymers and Cell, 2012)
Aim. The prostate tumor-inducing oncogene (PTI-1), presumably encoding a truncated form of eukaryotic translation elongation factor 1A1 (eEF1A1), was discovered as a gene overexpressed in prostate tumor samples and absent in normal tissues. The mechanism of PTI-1 oncogenicity remains obscure. Methods. Several bioinformatics methods were applied to analyze the PTI-1 mRNA structure, translation efficiency and coding potential. Results. In silico analysis of 5'UTR of its mRNA suggest that PTI-1 mRNA most probably belongs to the class of templates with low translation efficiency. Additionally, novel open reading frame (ORF) starting with alternative initiation site situated upstream of the main ORF start codon was found. Finally, the peptide that does not resemble eEF1A1 but is partially homologous to relaxin can be synthesized. Conclusions. We suggest that the alternative upstream start codon may initiate synthesis of a peptide (uPTI-1) homologous to relaxin, the hormone shown to promote the prostate cancer progression. uPTI-1 protein may interact with the respective relaxin-specific receptors, suggesting that the tumorigenic outcome of PTI-1 is possibly realized via the relaxin-dependent pathway. Keywords: prostate cancer, PTI-1, eEF1A1, non-coding RNA, relaxin, ORF, uAUG.